CD44+ Cells Influence Oral Squamous Cell Carcinomas in Two Comparative Age Groups - Villanueva-Sánchez, Francisco G. (2026)
Head and neck cancer (HNC) is the sixth most common malignancy worldwide, with high morbidity and mortality rates mainly due to delayed diagnosis. Cancer stem cells (CSCs) are involved in HNC progression and treatment response, carrying important therapeutic and prognostic implications. CD44, a transmembrane glycoprotein linked to cartilage, has been proposed as a CSC biomarker and is associated with cancer progression and poor survival. CSCs may also play a role in oral carcinogenesis among young individuals. This retrospective cross-sectional study aimed to identify CD44+ cells in oral squamous cell carcinoma (OSCC) across two age groups. Thirty-six OSCC cases from a teaching service for oral histopathological diagnosis were identified between January 2005 and December 2019. Cases were divided into two groups: young group (17 patients aged ≤ 40 years) and adult/elderly group (19 patients aged ≥ 41 years). Histological slides were obtained and stained using the hematoxylin and eosin technique and the immunohistochemical technique with anti-CD44 antibodies. In the young group, males predominated (70%) with the gingiva as the main site (9 cases), while the adult/elderly group had more females (52.5%), with eight cases on the tongue. Both groups primarily showed well-differentiated OSCC. In both groups, islands of CD44+ cells, characterized by large, basophilic nuclei and scant cytoplasm, were identified in the stroma. No significant association was found between CD44 immunoreactivity and age, sex, location, or differentiation degree (P > 0.05). The identification of CD44+ could contribute to improving the diagnosis and prognosis of oral cancer, and eventually offer targeted therapies.